(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
The design and synthesis of new polymer materials with controlled and predictable properties is still a challenge. Photoactive chromophore can be incorporated into a polymer in several different ways: guest-host systems, main chain polymers and side chain polymers. While none of these options are not perfect and each has its advantages and disadvantages. However, the chromophore functionalized polymers were found to be more effective due to: high concentration of the chromophores can be introduced; polymers with chromophore moiety show increased stability of poling induced SHG activity and decrease of the orientation relaxation process; absence of phase separation lessens the scattering losses; such techniques as plasma etching, optically induced index changes, laser ablation, electrical poling can be applied; multilayer phormation assists in easy integration with electronic and optical components. The principles of design of various molecular photoswitches and logical devices, in particular, those based on the photoisomerization reaction of diarylethylenes have been actively investigated in recent years. Azasubstituted diarylethylenes (DAE) styrylquinolines containing a central double bond and an endocyclic nitrogen atom, have become the subject of interest due to their ability to reversible transformations (photoisomerization and protonation). In this work, photosensitive polymers were synthesized by radical polymerization of corresponding styrylquinoline derivatives with comonomers methyl methacrylate (MMA) using asobisisobutyronitrile (AIBN) as radical initiator. We present results obtained for thin films of the methacrylic polymers incorporating styrylquinoline side-group as optically active molecule. Synthesis of 2-(4-methacryloxystyryl)quinolone and 2-(4-methacryloxystyryl)-6-methoxyquinoline was described. The polymers were obtained by free radical polymerization of methacrylic monomers in dimethylformamide with azobisisobutyronitrile as initiator. The products of polymerization were characterized and evaluated by 1HNMR, UV spectroscopy. Glass transition temperatures were characterized by DSC method. It was found 133°C, 110°C, 130°C, 112°C for P1, P1MMA, P2, P2MMA respectively. Their optical and photochemical properties as well as temperature dependence of the photoluminescence of diarylethylenes have been investigated.